The Problem-Solving Process Utilizing Drifting in Akina in the Anime Series Initial-D - Alfian Irfa Darajat; Andy Bangkit Setiawan (Badan Penerbit STIEPARI Press, 2023)
This research explores the process of adolescent problem resolution in Japan, specifically examining how drifting is employed as a means of conflict resolution among individuals within the context of the anime series titled